1991
DOI: 10.1139/z91-361
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen depletion in juvenile rainbow trout as an experimental test of the oxygen debt hypothesis

Abstract: Glycogen depletion was used as an experimental tool to examine the relationship between excess post-exercise oxygen consumption and lactate metabolism in 6-g rainbow trout. A 5-day starvation period reduced whole-body glycogen stores by 50% and slightly lowered resting lactate levels; resting oxygen consumption, glucose, ATP, and creatine phosphate levels were not affected. After a 5-min bout of exhaustive exercise, significantly less glycogen was utilized by the glycogen-depleted fish, 40% less lactate was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 20 publications
4
32
1
Order By: Relevance
“…Post-exercise oxygen consumption in swimming salmon stores could have limited anaerobic effort to some degree. However, while a 5·day starvation period has been shown to decrease total body glycogen stores and the accumulation of muscle lactate at exhaustion, it had no effect on EPOC (Scarabello et al, 1991). The third caveat is that we may have underestimated both EPOC and recovery time because of an elevated M .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Post-exercise oxygen consumption in swimming salmon stores could have limited anaerobic effort to some degree. However, while a 5·day starvation period has been shown to decrease total body glycogen stores and the accumulation of muscle lactate at exhaustion, it had no effect on EPOC (Scarabello et al, 1991). The third caveat is that we may have underestimated both EPOC and recovery time because of an elevated M .…”
Section: Discussionmentioning
confidence: 87%
“…The ramp-Ucrit protocol was repeated after this recovery period and EPOC was remeasured after the fish fatigued for a second time. (Brett and Groves, 1979;Scarabello et al, 1991). Total EPOC (mg·O2·kg -1 ) was obtained by integrating (Maple 8.00, Waterloo Maple Inc., Waterloo, ON, Canada) the area bounded between the recovery curve and M .…”
Section: Exercise Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, recovery time without a warm-down is >2·h for optimal performance on a time-to-exhaustion test (Mitton and McDonald, 1994). Wang et al (1994) reported that muscle phosphocreatine and ATP levels were restored within 30·min of rainbow trout being chased to exhaustion, while the post-exercise decline of oxygen consumption lasted 3-3.5·h (Scarabello et al, 1991). However, routine oxygen consumption does not have to be restored before adult sockeye salmon can repeat a second Ucrit test (Farrell et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…1). To deconvolute these signals, the first phase of the metabolic response was modelled using Eqn 2 (Scarabello et al, 1991):…”
Section: -2016042515065062 V2)mentioning
confidence: 99%